The Influence of the Concentration of Cyclohexane Radicals Bonded with an Si100 Silica Gel Surface upon the Retention of Some Hydrocarbons in Gas Chromatography - R. Nasuto (Adsorption Science & Technology)
Four adsorbents based on silica gel Si100 with chemically bonded cyclohexane have been prepared as stationary phases for gas chromatography. The concentrations of cyclohexane radicals thus bonded with the silica gel surface were 1.35, 3.35, 4.17 and 6.02 μmol/m 2 , respectively. Separation of aliphatic (C 6 –C 12 ), aromatic (benzene, toluene and m -xylene) and some polar organic compounds (chloroform, ethylene chloride, chlorobenzene, p -chlorotoluene and ethyl benzene) by gas chromatography using columns packed with the prepared adsorbents was studied. It was concluded that the retention of some compounds was increased on the column packed with an adsorbent of 1.35 μmol/m 2 concentration relative to that measured on the column packed with the unmodified silica gel. On columns packed with adsorbents with a higher bonded phase concentration than 1.35 μmol/m 2 , the retention times of all the compounds studied chromatographically decreased with an increase in the bonded phase concentration.